Crisis Monitoring and Response System - World Bank (Washington, DC, 2013)
This document contains a detailed description of the design, development, and operations of the Crisis Monitoring and Response System (CMRS). It covers the period from January 2009, when the CMRS was initiated, until September 2010 when the final CMRS reports (including this one) were completed. In addition to providing a definitive record of CMRS design and operational decisions, the document describes the results of the analyses based on the data collected. The document is intended to be the definitive source of reference material. It should prove particularly useful if and when consideration is given to the design, development and implementation of crisis monitoring system in the future. The ultimate objective was to ensure timely and appropriate policy responses in those districts identified as adversely affected as result of the global economic crisis (or any other shock). The output was to be an operational CMRS, comprising a data collection system and analyses that facilitated identification of appropriate responses. Funding for the CMRS was provided by Australian Government agency responsible for managing Australia's overseas aid program (AusAID). The level of funding determined the scale of the CMRS. The budget was sufficient to support three rounds of a survey collecting data via a relatively short questionnaire from about 15,000 households.